Factors Associated with Rabies Dog Vaccination Practices in Bebandem - I Nyoman Sudiatmika; Dewa Nyoman Wirawan; Made Pasek Kardiwinata (Public Health and Preventive Medicine Archive, 2016)
Background and purpose: The first reported case of rabies in Bali was in November 2008, wherein previously in Bali was declared rabies free. The epidemic spread rapidly to all district, including Karangasem regency. By December 2015 there were 163 reported rabies cases and all of them were infected through dog bites. It was estimated that there were 411,153 domestic canines in Bali. From 2009-2015 the immunization coverage in dog was reported 55.0-76.9%. This study aims to determine the proportion of households in the district of Bebandem that have vaccinated their dogs and the factors that influence the decision to vaccinate. Methods: The study was cross sectional and carried out in two villages in the district Bebandem with a sample of 110 families randomly selected. Data was collected through interviews regarding socio-demographic variables, knowledge, attitudes, perceptions, types of vaccination facilities, distance from vaccination facility and information received from the Departement of Agriculture/head of village. Multivariate analysis was done using poisson regression to determine the relationship between these variables with their dog vaccination for rabies. Results: Results indicated that 88% of households vaccinated their canine pets. Multivariate analysis showed that factors associated with the administration of the rabies vaccines were: having attended education session (APR=2.37; 95%CI: 1.34-4.18); family income (APR=1.16; 95%CI: 1.03-1.31); and perception (APR=3.09; 95%CI: 1.20-7.97). There was no significant relationship between education, knowledge and attitudes towards rabies vaccination in dog. Conclusion: Factors associated with dog rabies vaccination practice were having attended education session, family income and perception.